HUBUNGAN GURU KREATIF DAN INOVATIF DALAM PEMBELAJARAN DENGAN HASIL BELAJAR IPA SISWA KELAS V SDN 106833 DESA WONOSARI TANJUNG MORAWA DELI SERDANG - Heryanto Heryanto; Dita Fradilla (Universitas Quality, 2021)
This study aims to determine the description of creative and innovative teachers in learning, an overview of science learning outcomes, and the relationship between creative and innovative teachers in learning with science learning outcomes. The research was conducted at SD Negeri 106833, Wonosari Village, Tanjung Morawa, Deli Serdang Regency.As the population is all students in grade V and at the same time as the research sample totaling 44 students. The instruments used were questionnaires and documentation. The data analysis technique used is the analysis requirements test, namely the data normality test, regression linearity test, and hypothesis testing using the t-statistical test.The research results were obtained; (1) creative and innovative teachers in science learning with sufficient criteria with an average of 74.05; (2) Science learning outcomes have sufficient criteria with an average of 55.22; and (3) there is a significant relationship between creative and innovative teachers in learning with science learning outcomes.